The Relationship between Parenting Styles, Learning Motivation and Self-Efficacy of Diverse Age - Zeng, Shiya (Transactions on Social Science, Education and Humanities Research, 2024)
Linked to personal and national development, student education has long been regarded as an important project. In addition to school education, parental education at home also plays an essential role in students’ learning. Among previous research, there have been numerous studies on the relationship between parenting styles and students’ learning motivation and self-efficacy, but there have been relatively few studies comparing these situations across different grade groups. Therefore, this article adopts a review method to comprehensively compare five empirical researches on students of different school ages respectively, in order to explore the similarities and differences in the relation between parenting styles, learning motivation, and self-efficacy among students from different school ages, then provide a constructive reference for parental education. Research has found that overall, the results are approximately alike: parenting styles closely related to learning motivation and self-efficacy despite students from different school ages, and positive parenting styles significantly positively affect the learning motivation and self-efficacy of all school-age students while sometimes negative parenting styles also encourage self-efficacy.